2022
DOI: 10.56899/151.03.22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity in Côte d’Ivoire Cassava (Manihot esculenta Crantz) Using SSR Markers

Abstract: The aim of this study was to characterize the collection of cassava (Manihot esculenta) obtained from Côte d’Ivoire based on 14 microsatellite loci. Two hundred (200) accessions from five geographical zones – center, center-west, south, south-west, and west – were evaluated. High diversity values were found among the five above-mentioned regions, with 2.415 ± 0.153 alleles per locus on average. A high percentage of polymorphic loci varying from 38.46–100% was also observed. An average of 0.166 ± 0.026 for obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The average observed heterozygosity was similar to the results obtained by Kouakou et al [20] (Ho = 0.166) who evaluated 288 accessions from several regions of Côte d'Ivoire with 11 SSR markers. These observed heterozygosity values are low compared to those reported in the studies of Adjebeng-Danquah et al [7], which is equal to 0.42.…”
Section: Analysis Of Ssr Marker Polymorphismssupporting
confidence: 88%
See 1 more Smart Citation
“…The average observed heterozygosity was similar to the results obtained by Kouakou et al [20] (Ho = 0.166) who evaluated 288 accessions from several regions of Côte d'Ivoire with 11 SSR markers. These observed heterozygosity values are low compared to those reported in the studies of Adjebeng-Danquah et al [7], which is equal to 0.42.…”
Section: Analysis Of Ssr Marker Polymorphismssupporting
confidence: 88%
“…These observed heterozygosity values are low compared to those reported in the studies of Adjebeng-Danquah et al [7], which is equal to 0.42. Kouakou et al [20] reported that a low Ho value could be due to the use of fewer accessions and SSR markers. This was found in this study.…”
Section: Analysis Of Ssr Marker Polymorphismsmentioning
confidence: 99%